Relativistic electrons in photon fields - Effects of triplet pair production on inverse Compton gamma-ray spectra - Mastichiadis, A. (Monthly Notices of the Royal Astronomical Society, 1991)
Pair production of a photon in the Coulomb field of an electron (often referred to as triplet pair production) despite the fact that it is a third-order QED process has a cross-section that exceeds the Compton cross-section for energies of collision equal to or greater than 250 m(e)c-squared. The present paper reexamines the problem of ultrarelativistic electrons entering a photon field by including triplet pair production as both an energy loss and reinjection mechanism for electrons. The steady state electron distribution and photon spectrum are calculated for monoenergetic and power-law electron injections, and a comparison is made with the results obtained in the pure Compton case, i.e., by ignoring triplet pair production.
Keywords: Astrophysics; Compton Effect; Coulomb Collisions; Distribution Functions; Gamma Ray Spectra; Monte Carlo method; Pair Production; Photon-Electron Interaction; Relativistic Electron Beams; Steady State